Answers

2014-04-05T18:29:31+05:30
A^2+2b=7,b^2+4c=-7,c^2+6a=-14
addding all the three equations;we get
a^2+b^2+c^2+6a+4b+2c=7-7-14
a^2+b^2+c^2+6a+4b+2c=-14
a^2+b^2+c^2+6a+4b+2c+14=0
we can write this as;
a^2+6a+9+b^2+2b+1+c^2+4c+4=0
(a+3)^2+(b+1)^2+(c+2)^2=0
Hence; 
a+3=0,a=-3
b+1=0,b=-1
c+2=0,c=-2
therefore,a^2+b^2+c^2=(-3)^2+(-1)^2+(-2)^2
                                      =9+1+4
                                      =14....
a^2+b^2+c^2=14
2 3 2
u r gr8 sis
Tnks very much tisha......
dis is just brilliant!!! tahnx
*thanx
Thnx... Welcome......